The bawdy politic in Stuart England, 1660 - 1714: political pornography and prostitution - Mowry, Melissa (Women and gender in the early modern world, 2004)
The bawdy politic: and English common law -- The specter of corporate identity and 1668 -- Monstrous mothers: property and the common law -- Jades at livery and other prostitutes -- A citizen's duty and "common justice